A recent update on fucoidonase: source, Isolation methods and its enzymatic activity - Barzkar, Noora; Rungsardthong, Vilai; Tamadoni Jahromi, Saeid; Laraib, Qandeel; Das, Rakesh; Babich, Olga; Sukhikh, Stanislav (Frontiers in Marine Science, 2023)
Fucoidanases are hydrolytic enzymes that degrade fucoidan to a lower molecular weight while retaining the side substituent groups of the polymer. Fucoidanases are produced by marine organisms: bacteria, fungi, algae, molluscs, echinoderms. Fucoidanases are rare and little studied enzymes. There is currently no information on the structural organization of fucoidanases, the size of active centers, their secondary and tertiary structures. This review summarizes the data on fucoidanase sources and factors influencing fucoidanase activity. It was found that that such factors include medium pH, temperature, and the presence of metal ions. The principles of classification of fucoidanases were analyzed. Fucoidanase was found to have high biological activity. Fucoidanases are known to hydrolyze fucoidan to oligosaccharides that have anti-inflammatory, antiangiogenic, anticancer, antiviral, prebiotic, and anticoagulant properties. Thus, research into sources, isolation methods, the effect of fucoidanase on fucoidan, and its enzymatic activity is promising, and can be used to build the body’s resistance to adverse environmental factors (difficult working conditions, stress, and overwork), as well as restore and stimulate the immune response.